PENGARUH CARA EKSTRAKSI TERHADAP SIFAT FISIKA DAN KIMIA SAGU - R Sudradjat (Jurnal Penelitian Hasil Hutan, 1985)
The aim of this investigation is to evaluate  the effect of extraction methodes on physical  and chemical properties  of sago. Extraction  methodes  comprise  of  fermentation,  mechanical, and  traditional.The result indicated that sago yield varies from 20,19%  - 40,12%, acidity  0,89 - 0,98,  moisture  13,39% -14,29%, ash 0,15%  - 0,32%, protein 0,38%  - 0,46%, crude  fiber 0,27%  - 0,31%,  fat  0,17%  - 0,23%  and amylum  72,64%  - 88,12%.Mechanical  extractions  gave  the  highest  yield  and  amylum  content. Fermentation  methode  show more  acid  than traditional.  The traditional  methode presents the  highest ash content. This included that the mechanical methode  seemed to be preferable   for  commercial application.